O LUGAR DAS IDEIAS LIBERAIS NAS MEMÓRIAS PÓSTUMAS DE BRÁS CUBAS - Couto, Elvis Paulo [UNESP] (2020)
In his well-known book, A Master on the Periphery of Capitalism, Roberto Schwarz shows that the predominant formal principle, the volubility of the first-person narrator, in Machado de Assis's The Posthumous Memoirs of Brás Cubas was created to critically and ironically expose how Brazil was acclimating to liberalism. In addition to questioning the sociological implication of this argument, this paper aims to discuss the representation of liberal ideas in Machado's novel from the perspective that underlines the triumph of liberalism in the literary imagination.